Assessing Rodent Cardiac Function in vivo Using Hemodynamic Pressure-Volume Loops - Miranda-Silva, Daniela; Sequeira, Vasco; Lourenço, André P.; Falcão-Pires, Inês (Frontiers in Physiology, 2022)
Heart failure (HF) triggered by cardiovascular and non-cardiovascular diseases is a leading cause of death worldwide and translational research is urgently needed to better understand the mechanisms of the failing heart. For this purpose, rodent models of heart disease combined with in vivo cardiac functional assessment have provided valuable insights into the physiological significance of a given genetic or pharmacological modification. In small animals, cardiac function and structure can be evaluated by methods such as echocardiography, telemetry or hemodynamics using conductance catheters. Indeed, hemodynamic analysis of pressure-volume (PV) loops has become the gold standard methodology to study in vivo cardiac function in detail. This method provides simultaneous measurement of both pressure and volume signals from rodents intact beating hearts1-3. On the one hand, PV-loop analysis has deeply expanded the knowledge on molecular cardiac physiology by allowing establishing important functional correlations. On the other hand, these measurements allow dissecting the cardiovascular functional impact of certain therapeutic interventions or specific signalling pathways using transgenic models of disease. However, a detailed assessment of cardiac function and structure in vivo still warrants proper standardisation and optimisation to boost the progress of HF research. With increasing concerns over data accuracy and reproducibility, guidelines and best practices for cardiac physiology measurements in experimental settings are needed. This paper aims to describe how hemodynamics using PV-loop analysis represents an important technique to assess in vivo cardiac function, providing an overview of its advantages, disadvantages, applications and best practices for researchers in the cardiovascular field.